Incidentally detected renal leiomyosarcoma with inferior vena cava tumor thrombus: a case report with review of the literature - Wang, Puze; Li, Jinze; Liu, Qian; Lv, Dong; Liu, Liangren (Frontiers in Surgery, 2025)
Background: Kidney cancer is the 14th most common cancer worldwide. On the basis of the histological characteristics of kidney cancers, most kidney cancers are renal cell carcinomas. Renal leiomyosarcoma (LMS) is extremely rare and malignant and accounts for less than 1% of all kidney cancer cases. Our study aims to gain deeper insight into the pathological characteristics and synthesized treatment of this uncommon type. Thus, we conducted a retrospective analysis of one patient who was diagnosed with renal leiomyosarcoma and underwent comprehensive treatment at the People’s hospital of Deyang City.